Intellectual Capital of Islamic Boarding Schools to Build Multicultural Education Epistemology - Futaqi, Sauqi; Mashuri, Saepudin (EDUKASIA, 2023)
This research intends to discover the multicultural epistemology at Islamic boarding schools (pesantren). So far, Westerners and some university graduates have dominated the discourse on multicultural education, even though pesantren, with their distinctive intellectual capital, have their own perspectives on understanding, developing, and practicing multicultural education. Using phenomenological qualitative research on two pesantrens in Indonesia, this study uncovered that pesantrens have significant multicultural capital through personal, structural, or relational knowledge. For pesantren, multicultural education is not only an anthropological issue but rather a manifestation of the theology of humanity. Multicultural education for pesantren is a legacy of traditions of freedom of opinion, openness to differences, and the essence of humanity.